Hydrogel-derived soft materials for biomimetic and energy-related functions - Goudappagouda,; Wakchaure, V. C.; Ranjeesh, K. C.; Babu, S. S. (Australian Journal of Chemistry, 2016)
Supramolecular assembly of molecules leading to gelation of large amount of solvents is always a fascinating topic of research. In the very recent past, the exciting developments have marked hydrogels as intriguing materials with excellent features. Hydrogel scaffolds enable the accommodation of organic and/or inorganic guest materials to deliver diverse applications. Hydrogels have been exploited to generate soft materials with mechanical anisotropy, tunable rigidity, self-healing properties, as well as photocatalytic capabilities towards H2 production. Remarkably, the combination of a photocatalyst and a light-harvesting system in the gel matrix provides a unique means to photocatalytic H2 production. The biomimetic applications of hydrogels have also generated much attraction due to their potential demonstrations. The diverse applications underline the significance of such a soft gel medium to reach the final goal. Herein, important reports pertaining to the use of hydrogels as an effective way to generate advanced materials for biomimetic and energy-related issues are discussed.